Saudi Vision 2030 and the Challenge of Competitive Identity Transformation in Saudi Arabia - Leni Winarni; Aberrant Pratama Yoga Nur Permana (Universitas Muhammadiyah Yogyakarta, 2022)
Saudi Arabia’s founders inherited a legacy of oil wealth and conservative Islamic ideas in the Islamic world. Conversely, the crown prince seemed uninterested in preserving the heritage and attempted to change the tradition. Mohammed bin Salman, the crown prince of Saudi Arabia, wishes to transform the state’s conservative identity into a more moderate one. A main reason for the transformation is that Saudi can compete with other countries globally in developing various sectors. The crown prince initiated Saudi Vision 2030, a policy to establish a competitive identity and transform Saudi image globally, but that is not easy for Saudi, which is the heartland of religious conservatism and is likely to resist adopting transformation. Based on the statement above, this research explains how the crown prince tried to transform Saudi Arabia’s identity and build a different reputation through Saudi Vision 2030 became a contradiction in the Saudi government and society. The transformation and reconstruction of nation branding through Saudi Vision that promotes openness probably could eliminate the image of Saudi identity as a devout Islamic conservative. At the same time, this effort is a way to survive as a global economic actor without depending on the non-renewable energy sector. Finally, this paper found that norms, social and political culture, Saudi Arabia’s reputation, and Salman’s image hinder the construction of that identity.